HUBUNGAN TINGKAT KEPERCAYAAN DIRI DENGAN KETEPATAN SERVIS ATAS TIM BOLAVOLI PUTRA SMA NEGERI 13 SURABAYA TAHUN AJARAN 2017/2018 - Setya, Noviani Eka Budi (Jurnal Kesehatan Olahraga, 2018)
Volleyball is a big ball game played by two opposing teams, with six players on each team. Service is the most important basic techniques in volleyball game. There are two kinds of service in volleyball, namely upper service and bottom service. Self confidence is an attitude or a conviction within oneself so that others would not have any influence. It is expected that every player who do upper service have a high self confidence so that the service is done right on the target. The purpose of this study was to determine the relationship between confidence level of a volleyball team and the precision while doing upper service. This study is also aimed at determining the contribution of the level of confidence in the accuracy of the upper service. This type of research is descriptive quantitative where the were collected by distributing questionnaire about self confidence and the upper service accuracy test of the men volleyball team in 13 Senior High School of Surabaya which consists of 12 students. Based on calculations that have been done by using SPSS (StatisticalPackage for the SocialScience) 22 is the average value of questionnaire about self confidence which is 176 with a standard deviation of 9.352. The minimum value of the confidence variable is 156 and the maximum one is 192. Meanwhile the average value of the accuracy of the service on volleyball is 30.33 with 1.732 serves as the standard deviation. The minimum score of the service accuracy of volleyball is 28 and the maximum value is 33. The results of this study are as follows: 1) There is a strong relationship between the level of confidence with the accuracy of service within the men's volleyball team 13 Senior High School of Surabaya year 2017/2018. It is shown from the result of data calculation by using product moment correlation known r - count 0,626. 2) The percentage of the relationship between the confidence level and upper service accuracy of the men's volleyball team 13 Senior High School of Surabaya year 2017/2018 is 39.1%. Keywords : Confidence, Accuracy servicing over, Volleyball